Soluble DLL1 as an Indicator of acute kidney injury and postoperative delirium following cardiac surgery: a secondary analysis of a prospective study - Thomas Simon Zajonz; Fabian Edinger; Melanie Markmann; Anna-Lena Schreiner; Frauke Beckert; Markus A. Weigand; Florian Uhle; Bernd Niemann; Michael Sander; Christian Koch; Emmanuel Schneck (Perioperative Medicine)
Abstract Background Acute kidney injury (AKI) displays a common complication after cardiac surgery and must be diagnosed as early as possible. Soluble delta-like protein 1 (sDLL1) was originally evaluated as a sepsis biomarker but might also indicate other adverse outcomes. This study aims to investigate sDLL1 levels, examining its potential relationship with AKI and postoperative delirium (POD) after cardiac surgery and its predictive value. Methods This secondary analysis of a prospective observational trial included elective cardiac surgery patients. ELISA was used for the quantification of sDLL1. Statistical analysis involved repeated measures ANOVA and Pearson’s correlation to assess associations between sDLL1 levels, renal, and inflammatory parameters. Receiver operating curves were used for prediction analysis. Results Ninety patients were included in the study. Compared to patients without AKI, those with AKI (6.1%) showed significantly elevated plasma levels of sDLL1 postoperatively (no AKI 6308.49 [5121.27–7955.28], AKI 7,714.77 [7151.06–10,514.73] ng/mL; p = 0.01). Postoperative sDLL1 levels showed only a low predictive value for AKI (AUCROC 0.63, sensitivity 0.91, specificity 0.53). Postoperative sDLL1 measurements were also significantly elevated in patients with POD (23.3%). Further, postoperative sDLL1 plasma levels showed a moderate prediction for the identification of POD (AUCROC 0.72, sensitivity 0.64 specificity 0.73). Conclusion This study demonstrates that sDLL1 provides moderate predictive value for AKI and POD after cardiac surgery and may provide valuable insights into postoperative complications. sDLL1 levels increase independently of CPB type, suggesting a role in the inflammatory response to the cardiopulmonary bypass and surgical stress rather than specific renal injury. Trial registration DRKS00010959.